La crise des exceptions en droit d'auteur : étude paradigmatique - Piątek, Dariusz (Université d'Orléans, 2016)
La condition, la forme et la justification théorique des exceptions sont aujourd’hui au coeur du débat sur l’avenir du droit d’auteur. L’objectif primaire de ces normes particulières est de garantir la cohérence du droit d’auteur. Et pourtant les chercheurs s’accordent sur la nécessité de leur reconceptualisation.Cette thèse a pour but de découvrir la signification, les origines et les conséquences de la crise qu’engendre le ressentiment à l’égard des exceptions aux droits de l’auteur dans leur forme actuelle. Tenant compte d’une certaine fragilité axiologique de la matière, elle essaie d’appréhender les phénomènes étudiés selon une posture épistémologique neutre. À cet égard, la théorie des paradigmes scientifiques lui offre un cadre d’analyse scindé en deux. La reconstruction de l’état normal et voulu des principes élaborés par la tradition française du droit d’auteur en matière des exceptions permet de repérer les signes de leur dépassement par la réalité juridique mouvante.De cette analyse résulte d’abord le modèle d’une exception cohérente, internalisé par le droit d’auteur objectif qui a complètement résolu le conflit entre la création et la consommation des oeuvres de l’esprit. Cette image est ensuite confrontée à des forces destructrices ayant leur origine dans des normes extérieures au droit d’auteur objectif. Celles-ci se substituent aux exceptions prévues par le droit d’auteur et remettent en question l’idée de son autarcie.L’idylle du droit d’auteur autosuffisant n’est toutefois pas une utopie. Entre l’état normal et la maladie des exceptions se noue un lien dialectique. Vus ensemble, ces deux éléments s’éclairent réciproquement, de sorte que la crise qui les résume devient un processus réversible. The condition,shape and theoretical justification of copyright exceptions are at the heart of the debate on the future of copyright. The main objective of these particular rules is to ensure the consistency of copyright law. Yet, researchers agree on the need of their reconceptualization.This doctoral thesis aims to explore the meaning, origins and consequences of the crisis that brings resentment toward copyright exceptions in their present form. Taking into account a certain axiological fragility of the subject, it tries to apprehend it in the respect of a neutral epistemological posture. Therein, the theory of scientific paradigms offers a framework split in two. The reconstruction of the normal and wanted state of the principles developed by the French tradition of copyright in the field of exceptions allows to identify the signs of their violation by the changing legal reality.This analysis reveals, on the one hand, the model of a consistent exception, internalized by the copyright law which completely resolved the conflict between creation and consumption of works of the mind. On the other hand, this image is faced with the destructive forces that originate in the norms that are external to copyright law. These replace the copyright exceptions and, therefore, question the idea of its autarchy.The idyll of the self-sufficient copyright law is, however, not a utopia. A dialectical link can be traced between the normal state of exceptions and their illness.Seen together, these two elements illuminate each other, so that the crisis that summarize them becomes a reversible process.
Keywords: Antitrust; Competencia; Competition law; Concurrence; Contractual overridability; Contractualisation; Copyright; Crise; Crisis; Droit d'auteur; Droit d’auteur; Essential facilities; Exceptions; Exceptions (droit); Facilités essentielles; Freedom of speech; Intellectual property; Liberté d'expression; Mesures techniques de protection; Paradigm; Paradigme; Propriedade intelectual; Propriété intellectuelle; Technical protection measures

A critical review of the treatment of dominant firms in competition law : a comparative study - Munyai, Phumudzo S. (University of South Africa, 2016)
In South Africa compliance with competition law has become a major concern for firms that achieve and maintain certain levels of success and growth in the market, as their actions are often a source of complaints and litigation by rivals and competition authorities. With substantial financial penalties often levied against them for a variety of conduct deemed to constitute an abuse of their market position, dominant firms must constantly be aware of the likely impact of their business strategies and actions on both rivals and consumers. What were once thought to be normal and economically sound business practices and decisions, such as cutting prices to attract customers, have now acquired new meanings, with devastating consequences for dominant firms. So, are dominant firms under attack from competition law? In this study I aim to determine this. I track the historical development of competition law in three jurisdictions: South Africa, America, and the EU, with the aim of identifying traces, if any, of hostility towards dominant firms in the origins of competition law. I further investigate whether the formulation and enforcement of certain aspects of existing abuse of dominance provisions manifest as hostility towards dominant firms. While acknowledging the important role that competition law enforcement plays in promoting competition and enhancing consumer welfare, I conclude that significant unjustified economic and legal prejudice is suffered by dominant firms as a result of the way in which certain abuse of dominance provisions have been formulated and applied. I also offer appropriate recommendations.
Keywords: Abuse of dominance; Anti-monopoly; Anticompetitive effects; Anticompetitive harm; Antitrust law; Causation; Competencia; Competition Appeal Court; Competition Commission; Competition Tribunal; Competition law; Consumer harm; Consumer welfare; Counterfactual; Dominant firms; Exclusionary conduct; Hostility; Monopoly; Super-dominant; Unilateral conduct

Clauses et pratiques restrictives de concurrence - Fortunato, Aurelien (Université Lille 2, 2016)
Traditionnellement, le droit prend soin de distinguer entre les clauses, parties d’un acte juridique, et les pratiques qui sont des faits juridiques. Pourtant, le droit des pratiques restrictives de concurrence semble réaliser une assimilation de ces deux notions, en qualifiant de pratiques restrictives de concurrence certaines clauses. L’étude analyse cette qualification d’une clause en pratique en proposant un critère et en s’interrogeant sur ses effets : la possible contestation de clauses sur le fondement du droit des pratiques restrictives de concurrence. En invitant à une réflexion sur cet aspect du droit des pratiques restrictives de concurrence, il s’agit également de s’interroger sur les finalités de cette matière, autant que sur la possibilité d’une meilleure intégration de la contestation de clauses dans un droit des pratiques commerciales déloyales entre professionnels en construction.
Keywords: Clauses; Competencia; Competition law; Concurrence; Concurrence (droit); Concurrence déloyale; Contrats; Contrats (droit européen); Droit des contrats; Droit européen; Déséquilibre significatif; Pratiques commerciales déloyales; Pratiques restrictives de concurrence; Professionnels; Relations contractuelles; Restrictions à la concurrence; Équilibre contractuel

Análisis de los remedios públicos y privados en derecho de la competencia - Biffaro, Luca (Universitat Pompeu Fabra, 2016)
Este trabajo estudia los remedios antitrust que la Comisión Europea tiene el poder de imponer en el marco de su actividad de aplicación pública del Derecho de la competencia y asimismo analiza uno de los remedios que pertenecen al área del private antitrust enforcement, es decir el remedio indemnizatorio que los órganos jurisdiccionales nacionales pueden reconocer en favor de las víctimas de ilícitos concurrenciales en los supuestos de ejercicio, en forma autónoma o subsiguiente a la intervención administrativa, de una acción de indemnización por daños y perjuicios por incumplimiento de la normativa comunitaria de defensa de la competencia. En el trabajo se realiza antes de todo un encuadramiento general de ambas categorías de remedios en el ámbito del sistema de antitrust enforcement. Sucesivamente se desarrolla un análisis de los remedios públicos tanto desde el punto de vista teórico como a la luz de la praxis aplicativa comunitaria, recurriendo a una aproximación metodológica de tipo dogmático y económico. El trabajo, empleando una metodología parecida estudia los aspectos sustanciales y procesales del remedio indemnizatorio. El estudio de este remedio, en particular, se realiza arrancando de un breve análisis de la aplicación privada de la normativa antitrust en el ordenamiento estadounidense, del estado de desarrollo del private antitrust enforcement en Europa antes de la adopción, ratione materiae, de un Libro Verde por parte de la Comisión Europea, de las posiciones asumidas en el debate comunitario por los stakeholders españoles y del posible impacto del nuevo régimen armonizado en el ordenamiento jurídico español.
Keywords: Comisión Europea; Competencia; Competition law; Concurrence; Concurrence (droit); Derecho civil; Derecho de la competencia; Derecho mercantil

The Regulation of Promotional Competitions in South Africa - Strachan, Daniel Petrus (University of Pretoria, 2016)
Promotional competitions are competitions in which prizes are awarded by lot or chance in order to promote goods or services. Due to the chance element, these competitions are often categorised as lotteries or gambling. Initially, South African legislation did not make provision for the running of promotional competitions, but this situation changed when the Lotteries Act, 1997 came into force. Currently, promotional competitions are regulated by the Consumer Protection Act, 2008 (CPA). This thesis examines the regulation of promotional competitions in South Africa. It commences with a background discussion, which touches on the relevant terminology and some sociological aspects. It then considers the consequences of gambling and the need for and nature of regulation, and deals with the marketing and consumer protection contexts. This is followed by a brief overview of the global and South African history of gambling, lotteries and promotional competitions, which includes a discussion of South African case law. Foreign law relating to promotional competitions in New Zealand and Great Britain is explored in order to compare this to the South African position. This is followed by an examination of the current regulation of promotional competitions in South Africa, including a discussion regarding the interplay between the CPA and the Lotteries Act and a detailed analysis of the CPA’s provisions. The self-regulation of promotional competitions is discussed as well. The concluding chapter of this thesis contains recommended solutions for the problems identified in the analysis of the relevant legislation.
Keywords: Competencia; Competition law; Concurrence (droit); Consumer law; Droit de la consommation